2000
DOI: 10.1093/gerona/55.11.m634
|View full text |Cite
|
Sign up to set email alerts
|

Age Effects on the Temporal Evolution of Isometric and Swallowing Pressure

Abstract: Decreased lingual strength with age combined with unchanging swallowing pressure leads to a decreased "pressure reserve," perhaps leaving older individuals more at risk for dysphagia resulting from insults directly or indirectly to the swallowing system. Additionally, swallowing is generally "slowed" with age, apparently due to both central and peripheral factors, and this change may have an impact on bolus flow outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

36
309
5
8

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 347 publications
(358 citation statements)
references
References 33 publications
(45 reference statements)
36
309
5
8
Order By: Relevance
“…The pressure and the total work provided by the tongue 15 during the squeezing action of different jelly-type foods was recently studied (Yokoyama et al, 2014) and maximum pressures were measured in the range 5−40 kPa. Other groups (Nicosia et al, 2000;Youmans and Stierwalt, 2006) reported previously similar figures and highlighted also that pressure varies along the tongue position and is higher at the back. The mean peak tongue pressure 20 was also found to remain similar across different age groups, although maximum tongue strength was found to decrease with age (Youmans and Stierwalt, 2006;Utanohara et al, 2008).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…The pressure and the total work provided by the tongue 15 during the squeezing action of different jelly-type foods was recently studied (Yokoyama et al, 2014) and maximum pressures were measured in the range 5−40 kPa. Other groups (Nicosia et al, 2000;Youmans and Stierwalt, 2006) reported previously similar figures and highlighted also that pressure varies along the tongue position and is higher at the back. The mean peak tongue pressure 20 was also found to remain similar across different age groups, although maximum tongue strength was found to decrease with age (Youmans and Stierwalt, 2006;Utanohara et al, 2008).…”
supporting
confidence: 68%
“…Results (Yokoyama et al, 2014;Nicosia et al, 2000;Youmans and Stierwalt, 2006;Clavé et al, 2006). The movement of the roller induces a normal displacement of the soft membrane holding the liquid, toward the rigid top wall, similarly to the tongue approaching the palate.…”
Section: Theorymentioning
confidence: 96%
See 1 more Smart Citation
“…However, the Robbins et al exercise protocol focuses exclusively on strength and does not include actual swallowing tasks or other possible tongue-press tasks, such as those emphasizing precision, endurance, or speed. The fact that swallowing pressures are known to fall well short of those pressures registered in maximum isometric tasks [9] calls into question the emphasis on strength goals and outcomes in this approach.…”
Section: Introductionmentioning
confidence: 99%
“…For the current study, we studied partial-pressure amplitude targets in the range of 50 percent of each participant's maximum isometric pressure capacity (henceforth called "half-maximum tongue-palate press" tasks). The choice of this target range was motivated by previous evidence showing that habitual swallowing pressures typically fall in or below this halfmaximum range [9].…”
Section: Introductionmentioning
confidence: 99%